Ignited minds : unleashing the power within India - Kalam, A. P. J. Abdul (New Delhi ; New York, NY : Viking, 2002)
Autobiographical account of the author focused on the development of India
Includes bibliographical references and index.
Keywords: Twenty-first century -- Forecasts; Patriotism -- India; Motivation (Psychology) in adolescence -- India